Mygalomorph spiders from southwestern Oregon, USA, with descriptions of four new species - Cokendolpher, James C.; Peck, Robert W.; Niwa, Christine G. (Zootaxa, 2005)
Extensive pitfall trapping in the Siskiyou and southern Cascade Mountains in southwestern Oregon, USA, revealed the presence of four new species of Antrodiaetus spiders (Antrodiaetidae) as well as numerous examples of the rarely reported Hexura rothi (Mecicobothriidae). The new species are: Antrodiaetus ashlandensis, A. coylei, A. effeminatus, and A. metapacificus. Additional records were also obtained for Antrodiaetus pugnax and Atypoides gertschi (Antrodiaetidae). Distributional data are provided for each species. The four new species are described and illustrated and a taxonomic key to all mygalomorph spiders from southwestern Oregon is provided. Further, each of the previously described Antrodiaetus spp. from the region is diagnosed. The morphology of the male genital plate is proposed as a potentially useful taxonomic character.